Analisis Kandungan Tembaga (Cu) Dari Limbah Cair Pencucian Bauksit Di Kecamatan Tayan Hilir Dan Meliau, Kabupaten Sanggau, Kalimantan Barat - Octadinata, Rizky; Gusmayanti, Evi; Ali Akbar , Aji (Riviera Publishing, 2025)
One of the impacts of the bauxite washing process is liquid waste. Waste that is not managed properly and is thrown into surface water (rivers) will cause various impacts that will cause environmental damage and harm the people living around the mining location. The aim of this research is to determine the Copper (Cu) content found around the river which is the recipient of waste from bauxite washing waste by taking samples at 30 sample points. Cu analysis using Atomic Absorption Spectrophotometer (AAS). The results of the laboratory test analysis were compared with the Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management and statistical analysis tests were carried out using the Kruskal Wallis test. The research results show that the Copper (Cu) content ranges from 0.03 – 0.05 mg/L, this value is above the environmental quality standard value. The statistical test results also show that there is no difference in the average Copper (Cu) content between the three research locations both in the morning and evening.